Healthy Living: Monitoring Blood Pressure at Home - Karla P. Shelnutt (EDIS)
FCS8882, a 2-page fact sheet by Karla P. Shelnutt, provides instructions and explanations of blood pressure readings, along with a blank blood pressure log. Published by the UF Department of Family Youth and Community Sciences, November 2009.